Efficiency of nutrient utilization by Nelore and Canchim breeds, and Holstein-zebu crossbreed heifers - Manzano, Airton; Novaes, Nelson José; Esteves, Sérgio Novita (Pesquisa Agropecuaria Brasileira, 2014)
This study aimed at providing livestock farmers adequate feeding systems to Nelore and Canchim breeds, and Holstein-Zebu crossbreed growing heifers. All animals received, during a certain period, three types of ration, with the following proportions of roughage concentrate: 30/70 (R1), 50/50 (R2) and 60/40 (R3). The concentrate contained 18% crude protein (CP) and sugarcane was used as the roughage source. Thirty nine heifers were used, thirteen from each breed or crossbreeding, with and average weight of 210 kg and twelve months of age. The marker method (Cr2O3) was used for digestibility coefficient determination using a fourteen day pre-experimental period and a seven day experimental period. A significant (P<0.01) breed x ration interation was observed for the crude fiber (CE) digestibility. Nelore tended to be superior to Canchim and crossbreed in utilization efficiency of dry matter, cellulose and gross-energy in ration R1, In rations R2 and R3, there was and opposite tendency. CP digestibility was significantly (P<0.01) higher for the crossbreed than for the Nelore breed in all these rations. There was a tendency for the Nelore breed to retain less nitrogen, as the proportion of concentrate increased, as opposed to that in the crossbreed and Canchim heifers.